Vertical price transmission: a case of integrated Malaysian broiler industry - Muazu, Abdulrazak Umar; Mohamed , Zainal Abidin; Shamsudin, Mad Nasir; Abd. Latif, Ismail (Global Journals, 2014)
This paper examines how price changes are transmitted between farm-wholesale-retail market levels of broiler meat in Peninsular Malaysia. Data used in the analysis include average monthly farm, wholesale and retail price index for standard broiler meat for period 2000M01 through 2011M12. Johansen’s and Juselius co-integration technique was used to examine whether long run relationship between the price indices exists. Asymmetry error correction model was used to analyze price transmission behavior along the vertical supply chain. The results indicate there is long run equilibrium relationship between the market price levels. The results of price transmission elasticity show retail responds to wholesale 0.943% and retail to farm 0.0284%. The sign of the value of ECT is negative (-0.659) and significant at 5% significance level implying an ECT towards equilibrium is expected. The formal test of asymmetry proved symmetric price transmission retail-wholesale and asymmetry behavior retail to farm.